PENGARUH MOTIVASI, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TIRTA INVESTAMA - Ni Made Ari Purnami; I Wayan Mendra; Tjok Istri Sri Harwathy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
PT Tirta Investama Bali is able to maintain its existence until now. To maintain this existence, it is necessary to have competent human resources in carrying out company performance. This study aims to determine the effect of motivation, job satisfaction, and work discipline on employee performance. This research was conducted at PT. Tirta Investama in Mambal using a sample of 45 employees as research respondents. The sampling technique used was the census method. Data collection was carried out through interviews and questionnaires. The data analysis technique used is multiple linear regression analysis which is processed using SPSS version 23 software. Based on the results of the analysis, this study shows that motivation has a positive and significant effect on employee performance, so that the higher the motivation, the higher the employee's performance. Job satisfaction has a positive and significant effect on employee performance, so that the higher the job satisfaction, the higher the employee's performance. Work discipline has a positive and significant effect on employee performance, so that the higher the work discipline, the higher the employee's performance.